A picture tells a thousand words: what Facebook and Twitter images convey about our personality - Whitty, Monica Therese; Doodson, James; Creese, Sadie; Hodges, Duncan (Elsevier, 2017)
Researchers have questioned whether there is a relationship between personality and patterns of online self-presentation. This paper examined, more specifically, whether personality predicts profile choices as well as image choice behaviour on two different SNSs: Twitter and Facebook. We found that personality does, to some extent, predict choices regarding profile images; however, not always in the direction we predicted and results differed across sites. We found that participants who scored higher on conscientiousness and lower on extraversion were more likely to change their Facebook profile image. Participants who scored lower on extraversion were more likely to choose a Twitter profile image that included a photograph of themselves compared to participants who scored higher on extraversion. For participants whose Facebook profile image was a photograph of themselves, a greater proportion of participants selected a recent photograph from the past six months. However, this was not the case for Twitter. We conclude that personality can predict some image choices and behaviours that might be useful for future work on authentication and identification, although other predictor variables are potentially also important when considering the types of individual characteristics which might predict online behaviour on SNSs.
Keywords: Cyberpsychology; Personality; Profile images; Big Five; Social network sites; Facebook; Twitter